A modified polypropylene film, preparation method and application in capacitors
By using the nuclear shell structure organic inorganic hybridization due to the use of the nuclear shell structure in the polypropylene capacitor film, the problem of the existing technical intermediary electricity constant increased the problem of the increase with the increase in the loss of the medium, and realized the improvement of the dielectric constant and the decrease in loss consumption. Both effect.
Patent Information
- Application Number
- CN202411496121.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-25
AI Technical Summary
While the existing polypropylene capacitor film increases dielectric constant, dielectric loss increases, resulting in a decrease in charge-discharge efficiency and an increase in energy loss, which cannot meet the requirements of power capacitors.
The core-shell structure organic-inorganic hybrid dielectric filler is used to dielectrically modify the polypropylene substrate, and an azo initiator with a coupling function and a non-polar long alkyl chain group is synthesized and anchored to titanate The surface of barium nanoparticles triggers free radical polymerization of vinyl monomers to form a core-shell structure organic-inorganic hybrid dielectric filler.
The dielectric average of the modified polyacrylin film is significantly improved to more than 20, and at the same time, it effectively suppresses the dielectric loss, reduced to less than 0.005, improved the charging-discharge efficiency and reduced energy loss.
Smart Images

Figure SMS_1 
Figure QLYQS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of dielectric films, in particular to a modified polypropylene film, a preparation method and application in capacitors. Background Art
[0002] Polypropylene capacitor film made of polypropylene as the base material is a high-frequency and alternating-frequency dielectric insulating material with excellent electrical properties. It has the advantages of small dielectric loss, dielectric constant that does not change with frequency, excellent moisture resistance, and low price. Therefore, it has become an important basic dielectric material in the capacitor manufacturing industry. In order to improve the defect of low dielectric constant of polypropylene, using high dielectric constant barium titanate and polypropylene to make barium titanate / polypropylene composite film is an effective way.
[0003] However, existing studies have shown that while increasing the dielectric constant, it often brings about a surge in dielectric loss. The surge in dielectric loss will significantly reduce the charge-discharge efficiency and cause a large amount of energy loss, which cannot meet the requirements of power capacitors. In addition, nanoparticles with high surface energy tend to agglomerate in the polymer matrix, resulting in a decrease in the overall performance of the nanocomposite medium. Summary of the invention
[0004] The present invention independently develops a method for preparing a modified polypropylene film, which utilizes a core-shell structured organic-inorganic hybrid dielectric filler to perform dielectric modification on a polypropylene substrate to prepare a modified polypropylene film, which can be used as a dielectric film of a metallized film capacitor in the capacitor manufacturing industry.
[0005] A method for preparing a modified polypropylene film comprises the following steps:
[0006] Step S1, preparing a core-shell structure organic-inorganic hybrid dielectric filler, the specific process is as follows:
[0007] Step S1-1, 4,4'-azobis(4-cyanovaleric acid) first undergoes a nucleophilic substitution reaction with 1-chlorododecane in the presence of triethylamine to generate a monoester, and then undergoes an esterification reaction with 3-chloropropyltrimethoxysilane to synthesize an azo initiator having a coupling function and containing a non-polar long alkyl chain group;
[0008] Step S1-2, the silanol functional groups obtained by the hydrolysis reaction of the hydrolyzed functional groups of the azo initiator synthesized in step S1-1 undergo a dehydration condensation reaction with the hydroxyl functional groups on the surface of the hydroxylated barium titanate nanoparticles, thereby anchoring the azo initiator to the surface of the barium titanate nanoparticles, thereby obtaining barium titanate nanoparticles with the azo initiator containing a non-polar long alkyl chain group anchored on the surface;
[0009] Step S1-3, using an azo initiator to initiate free radical polymerization of olefin monomers on the surface of barium titanate nanoparticles, and grafting polymer molecular chains to the surface of barium titanate nanoparticles by covalent bonds to obtain a core-shell structured organic-inorganic hybrid dielectric filler;
[0010] Step S2, preparing ingredients according to the formula of the modified polypropylene film;
[0011] The modified polypropylene film has a formula of: 100 parts by weight of polypropylene resin, 1-10 parts by weight of a compatibilizer, 0.1-0.5 parts by weight of an antioxidant, and 3-15 parts by weight of a core-shell structured organic-inorganic hybrid dielectric filler;
[0012] Step S3, melt-blending the ingredients of the modified polypropylene film, and pressing the mixture into shape by hot pressing to obtain the modified polypropylene film.
[0013] Preferably, in step S1-1, the molar ratio of 4,4'-azobis(4-cyanovaleric acid), 1-chlorododecane and 3-chloropropyltrimethoxysilane is 1:(1.01-1.09):(1.05-1.2).
[0014] Preferably, in step S1-2, the mass ratio of the hydroxylated barium titanate nanoparticles to the azo initiator having a coupling function and containing a non-polar long alkyl chain group is 1:(0.3-0.9).
[0015] Preferably, in step S1, the mass ratio of the barium titanate nanoparticles with the azo initiator containing non-polar long alkyl chain groups anchored on the surface to the olefin monomer is 1:(2.5-5.5).
[0016] Preferably, the average size of the barium titanate nanoparticles used to hydroxylate the barium titanate nanoparticles in step S1-2 is 100-200 nm.
[0017] Preferably, the olefin monomer in step S1-3 is one of 2-methoxyethyl acrylate, methyl methacrylate and styrene.
[0018] Preferably, the compatibilizer in step S2 is one of polypropylene grafted maleic anhydride PP-g-MAH, silane grafted polypropylene VTMS-g-PP, and maleic anhydride / silane grafted polypropylene MAH / VTMS-g-PP.
[0019] Preferably, the antioxidant in step S2 is antioxidant 1010 or antioxidant 1076.
[0020] Preferably, the process parameters of the hot pressing method in step S3 are: temperature 180-220° C., pressure 10-20 MPa, and time 10-30 min.
[0021] The modified polypropylene film prepared according to the method has a thickness of 1-2 mm, a relative dielectric constant of 20.3-22.7, and a dielectric loss of 0.0014-0.0042.
[0022] Compared with the prior art, the present invention has the following beneficial technical effects:
[0023] An azo initiator with coupling function and nonpolar long alkyl chain group was synthesized;
[0024] On the one hand, the silanol functional groups obtained by the hydrolysis reaction of the azo initiator through the hydrolysis functional group undergo a dehydration condensation reaction with the hydroxyl functional groups on the surface of the hydroxylated barium titanate nanoparticles, and the azo initiator containing a non-polar long alkyl chain group is anchored to the surface of the barium titanate nanoparticles. The azo initiator initiates free radical polymerization of olefin monomers on the surface of the barium titanate nanoparticles, and the polymer molecular chains are grafted to the surface of the barium titanate nanoparticles by a covalent bond method, thereby obtaining a core-shell structured organic-inorganic hybrid dielectric filler;
[0025] The barium titanate nanoparticles with a complete coating layer on the surface can not only effectively hinder the migration of charges on the barium titanate surface, reduce leakage current and loss, but also significantly improve the dispersion performance of the barium titanate nanoparticles in the polypropylene matrix;
[0026] On the other hand, the azo initiator anchored on the surface of barium titanate nanoparticles can utilize non-polar long alkyl chain groups to be physically entangled with the non-polar polypropylene matrix, thereby improving the compatibility of barium titanate nanoparticles with the polypropylene matrix.
[0027] The core-shell structured organic-inorganic hybrid dielectric filler was used to perform dielectric modification on the polypropylene substrate to prepare a modified polypropylene film. The experimental results showed that the dielectric constant of the modified polypropylene film was increased to above 20 and the dielectric loss was reduced to below 0.005.
[0028] The invention achieves the beneficial technical effect of effectively suppressing the dielectric loss of the modified polypropylene film while significantly improving the dielectric constant of the polypropylene matrix. DETAILED DESCRIPTION
[0029] Embodiment 1: A modified polypropylene film comprises the following raw materials in parts by weight:
[0030] Polypropylene resin, 100 parts;
[0031] Polypropylene grafted maleic anhydride PP-g-MAH, 5 parts;
[0032] Antioxidant 1010, 0.3 parts;
[0033] Core-shell structure organic-inorganic hybrid dielectric filler, 8 parts;
[0034] The preparation method of the core-shell structure organic-inorganic hybrid dielectric filler is shown in the following experimental example.
[0035] Embodiment 2: A method for preparing a modified polypropylene film, comprising the following steps:
[0036] Step 1, preparing polypropylene resin: polypropylene pellets (purchased from Shanghai Tingyuan Plastic Technology Co., Ltd., brand HJ730) were dissolved in a xylene solution at a mass ratio of 1:40, stirred at a constant temperature of 160°C for 3 hours, filtered and placed in a vacuum drying oven at 70°C for 6 hours to obtain polypropylene resin;
[0037] Step 2, preparing a modified polypropylene film: According to the formula of the modified polypropylene film in Example 1, the core-shell structured organic-inorganic hybrid dielectric filler, polypropylene grafted maleic anhydride PP-g-MAH, antioxidant 1010 and polypropylene resin are melt-blended at 190° C. and 60 rpm for 10 min, and the mixture is pressed and molded by hot pressing at a temperature of 190° C., a pressure of 15 MPa, and a time of 30 min to obtain a modified polypropylene film with a thickness of about 1.5 mm.
[0038] Example 3: Dielectric performance test: The dielectric loss and capacitance C of the modified polypropylene film sample prepared in Example 2 (the silver electrode was sputtered on the sample surface by a magnetron ion sputtering instrument) were tested using a dielectric spectrometer, and the test frequency was 100Hz-1MHz;
[0039] According to the capacitance C, the relative dielectric constant ε of the sample is calculated by the following formula (1):
[0040] ε=(C×d)÷(ε0×A) (1)
[0041] Where: C represents capacitance, unit is F;
[0042] d represents the thickness of the sample, in m;
[0043] A represents the surface area of the sample, in m 2 ;
[0044] ε0 represents the dielectric constant of vacuum, ε0=8.854×10 -12 F / m;
[0045] The above test results are shown in Table 1 below;
[0046] Table 1 Experimental results of dielectric properties of modified polypropylene films
[0047]
[0048] Note: At test frequency 10 2 Hz-10 5At Hz, the relative dielectric constant of pure polypropylene film was tested to be 1.86-1.88 and the dielectric loss was 0.00014-0.00029;
[0049] At test frequency 10 2 Hz-10 5 At Hz, the dielectric constant of the barium titanate / polypropylene composite film was tested to be 15.9-18.2 and the dielectric loss was 0.013-0.057;
[0050] The difference between the pure polypropylene film and the modified polypropylene film in Example 2 is that: no core-shell structure organic-inorganic hybrid dielectric filler is added;
[0051] The difference between the barium titanate / polypropylene composite film and the modified polypropylene film in Example 2 is that the core-shell structure organic-inorganic hybrid dielectric filler is replaced by directly purchased raw barium titanate particles (barium titanate BaTiO3, with an average size of 100 nm);
[0052] The experimental results show that the dielectric modification of polypropylene substrate using core-shell structured organic-inorganic hybrid dielectric fillers can effectively improve the dielectric constant of the polypropylene substrate while playing a technical role in effectively suppressing the dielectric loss of the modified polypropylene film.
[0053] Experimental example:
[0054] The method for preparing a core-shell structure organic-inorganic hybrid dielectric filler comprises the following steps:
[0055] Preparation of hydroxylated barium titanate nanoparticles: 10 g of barium titanate particles (BaTiO3, average size of 100 nm) and 60 mL of hydrogen peroxide (30 wt%) were added to a flask, ultrasonically dispersed for 1 h, refluxed at 105 °C for 4 h, centrifuged at 9000 rpm for 10 min, washed with deionized water, and vacuum dried at 80 °C for 12 h to obtain hydroxylated barium titanate nanoparticles;
[0056] An azo initiator having a coupling function and containing a non-polar long alkyl chain group is synthesized, and its specific mechanism is as follows: 4,4'-azobis(4-cyanovaleric acid) first undergoes a nucleophilic substitution reaction with 1-chlorododecane in the presence of triethylamine to generate a monoester, and then undergoes an esterification reaction with 3-chloropropyltrimethoxysilane, and the molar ratio of 4,4'-azobis(4-cyanovaleric acid), 1-chlorododecane and 3-chloropropyltrimethoxysilane is controlled to be 1:1.06:1.1, thereby obtaining an azo initiator having a coupling function and containing a non-polar long alkyl chain group, and its chemical structure is as follows:
[0057] ;
[0058] The experimental steps for synthesizing an azo initiator having a coupling function and containing a non-polar long alkyl chain group are as follows: 2.8 g of 4,4'-azobis(4-cyanovaleric acid), 2.5 mL of 1-chlorododecane, 1.5 mL of triethylamine and 40 mL of N,N-dimethylformamide are added to a three-necked flask, stirring is started, and the mixture is reacted at 85°C for 4 h, then 2 mL of 3-chloropropyltrimethoxysilane and 1.5 mL of triethylamine are added to the flask, the mixture is reacted at 80°C for 2 h, the mixture is cooled to room temperature, washed with deionized water, filtered, the product is precipitated with methanol, the methanol is removed by rotary evaporation, and the mixture is vacuum dried at 60°C for 12 h to obtain an azo initiator having a coupling function and containing a non-polar long alkyl chain group;
[0059] The hydrogen spectrum characterization results of the azo initiator with coupling function and non-polar long alkyl chain group are as follows: 1 HNMR (400MHz, DMSO-d6, δ, ppm): 0.59-0.72 (m, 2H), 0.86-0.91 (t, 3H), 1.20-1.42 (m, 18H), 1.49-1. 61(m, 8H), 1.74-1.85(m, 2H), 2.19-2.33(m, 4H), 2.38-2.45(m, 4H), 3.57(s, 9H), 4.01-4.13(m, 4H);
[0060] Preparation of surface-grafted azo initiator barium titanate nanoparticles: 10 g of hydroxylated barium titanate nanoparticles and 80 mL of anhydrous toluene were added to a flask, ultrasonically dispersed for 1 h, 5 g of an azo initiator having a coupling function and containing a non-polar long alkyl chain group was added, nitrogen was passed, refluxed at 80° C. for 24 h, centrifuged at 9000 rpm for 10 min, washed with anhydrous toluene, and vacuum dried at 80° C. for 12 h to obtain surface-grafted azo initiator barium titanate nanoparticles;
[0061] Preparation of core-shell structured organic-inorganic hybrid dielectric fillers: 2 g of barium titanate nanoparticles with surface grafted azo initiator and 40 mL of N,N-dimethylformamide were added to a flask, ultrasonically dispersed for 1 hour, 20 mL of N,N-dimethylformamide solution containing 10 g of methyl methacrylate was added, nitrogen was passed through, stirred and reacted at 50°C for 24 hours, centrifuged at 9000 rpm for 10 minutes, precipitated with acetone, and vacuum dried at 80°C for 12 hours to obtain core-shell structured organic-inorganic hybrid dielectric fillers.
Claims
1. A method for preparing a modified polypropylene film, characterized in that: The following steps are involved: Step S1, preparing a core-shell structure organic-inorganic hybrid dielectric filler, the specific process is as follows: Step S1-1, 4,4'-azobis(4-cyanovaleric acid) first undergoes a nucleophilic substitution reaction with 1-chlorododecane in the presence of triethylamine to generate a monoester, and then undergoes an esterification reaction with 3-chloropropyltrimethoxysilane to synthesize an azo initiator having a coupling function and containing a non-polar long alkyl chain group. The chemical structure of the azo initiator is: ; Step S1-2, the silanol functional groups obtained by the hydrolysis reaction of the hydrolyzed functional groups of the azo initiator synthesized in step S1-1 undergo a dehydration condensation reaction with the hydroxyl functional groups on the surface of the hydroxylated barium titanate nanoparticles, thereby anchoring the azo initiator to the surface of the barium titanate nanoparticles, thereby obtaining barium titanate nanoparticles with the azo initiator containing a non-polar long alkyl chain group anchored on the surface; Step S1-3, using an azo initiator to initiate free radical polymerization of olefin monomers on the surface of barium titanate nanoparticles, and grafting polymer molecular chains to the surface of barium titanate nanoparticles by covalent bonds to obtain a core-shell structured organic-inorganic hybrid dielectric filler; Wherein, the vinyl monomer is methyl methacrylate; Step S2, preparing ingredients according to the formula of modified polypropylene film; The modified polypropylene film has a formula of: 100 parts by weight of polypropylene resin, 1-10 parts by weight of a compatibilizer, 0.1-0.5 parts by weight of an antioxidant, and 3-15 parts by weight of a core-shell structured organic-inorganic hybrid dielectric filler; Step S3, melt-blending the ingredients of the modified polypropylene film, and pressing the mixture into shape by hot pressing to obtain the modified polypropylene film.
2. The method for preparing a modified polypropylene film according to claim 1, characterized in that: In step S1-1, the molar ratio of 4,4'-azobis(4-cyanovaleric acid), 1-chlorododecane and 3-chloropropyltrimethoxysilane is 1:(1.01-1.09):(1.05-1.2).
3. The method for preparing a modified polypropylene film according to claim 1, characterized in that: In step S1-2, the mass ratio of the hydroxylated barium titanate nanoparticles to the azo initiator having a coupling function and containing a non-polar long alkyl chain group is 1:(0.3-0.9); In step S1, the mass ratio of barium titanate nanoparticles with azo initiators containing non-polar long alkyl chain groups anchored on the surface to olefin monomers is 1:(2.5-5.5).
4. The method for preparing a modified polypropylene film according to claim 1, characterized in that: The average size of the barium titanate nanoparticles used for hydroxylating the barium titanate nanoparticles in step S1-2 is 100-200 nm.
5. The method for preparing a modified polypropylene film according to claim 1, characterized in that: In step S2, the compatibilizer is one of polypropylene grafted maleic anhydride PP-g-MAH, silane grafted polypropylene VTMS-g-PP, and maleic anhydride / silane grafted polypropylene MAH / VTMS-g-PP.
6. The method for preparing a modified polypropylene film according to claim 1, characterized in that: In step S2, the antioxidant is antioxidant 1010 or antioxidant 1076.
7. The method for preparing a modified polypropylene film according to claim 1, characterized in that: The process parameters of the hot pressing method in step S3 are: temperature 180-220° C., pressure 10-20 MPa, and time 10-30 min.
8. A modified polypropylene film prepared by the method according to any one of claims 1 to 7, characterized in that: The thickness of the modified polypropylene film is 1-2 mm, the relative dielectric constant is 20.3-22.7, and the dielectric loss is 0.0014-0.0042.
9. The use of a modified polypropylene film according to claim 8, characterized in that: Modified polypropylene film is used as dielectric film for metallized film capacitors in the capacitor manufacturing industry.
Citation Information
Patent Citations
Polymer-based dielectric energy storage composite film material with core-shell structure and preparation method
CN105315587A
Modified barium titanate nano-particle, preparation method thereof, modified polymer composite film and preparation method of film
CN108410016A